Design of Lending System Using Topsis Method at Koperasi PT Nagasakti Paramashoes Industry - Willian Apredo; Adiyanto Adiyanto; Masduki Asbari (UJoST- Universal Journal of Science and Technology, 2022)
PT Nagasakti Paramashoes Industry is a company engaged in the Shoe Industry. In the company, there is a savings and loan cooperative that records special transaction activities for employees at PT Nagasakti Paramashoes Industry. Cooperatives are one of the aspects that support the community's economy, especially low- and middle-income employees. This existing cooperative needs to be developed so that the cooperative can provide good service to employees. Savings and Loans Cooperative PT Nagasakti Paramashoes Industry is one of the cooperatives that helps support the economy of employees by providing savings and loan services with low-interest rates. Of the many transactions in the savings and loan cooperatives of PT Nagasakti Paramashoes Industry, no system can manage it in detail so it makes it difficult for the company to record transaction reports so errors often occur in the data processing. The design of an information system using the topsis method at PT Nagasakti Paramashoes Industry is an application that makes it easy for employees to provide loans based on 5 predetermined criteria.